An Estimation of the Efficiency of Public Research Institutes in Poland: The DEA Approach - Brzezicki, Łukasz; Prędki, Artur (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: The purpose of this paper is to measure and assess the efficiency of research institutes in Poland. The institutes operate on the basis of various legal frameworks, but they serve a common purpose and have a joint area of activity, research and development. Research Design & Methods: We used the SBM model, a component of the non-parametric Data Envelopment Analysis (DEA) methodology, to analyse the efficiency of research institutes in 2019. The Metafrontier approach was also employed to verify whether the above different legal framework had an impact on the functioning of the entities under analysis. Findings: Histograms of the efficiency measure indicate a large dispersion of its value. In particular, a significant fraction of units is characterised by extremely high values of this measure. Average MTRs, calculated using the Metafrontier approach, are mostly significantly lower than one. Implications / Recommendations: The obtained results indicate that groups of institutes with different legal framework function differently. Moreover, a large proportion of the objects analysed is characterised by significant inefficiency within the area of R&D. The paper lists the potential reasons, which will be the object of further, in-depth research. Contribution: The research constitutes a preliminary attempt to analyse and evaluate the efficiency of research institutes in Poland after the introduction of the last reform of the science and higher education system in 2018, as such studies have not been carried out to date. It is also essential to use the Metafrontier approach within the DEA methodology in order to model differences in the functioning of three different groups of research institutes in Poland.